Composites from biodegradable and biocompatible methylcellulose, poly(d, l‐lactide‐co‐glycolide) and poly(1, 4‐butylene succinate) with enhanced properties. Issue 18 (27th November 2020) - Xu, Airong; Wang, Fen; Zhang, Luwei; Xu, Xingmin; Xiao, Zhihong; Liu, Rukuan
Abstract: Polymer materials based on fossil resources have brought great convenience to various industries. However, environmental pollution is becoming increasingly conspicuous due to their difficult degradation in nature. Therefore, biodegradable composites are highly desired. In the present work, a simple and feasible preparation approach was presented to fabricate biodegradable and biocompatible composite films including methylcellulose/poly(d, l ‐lactide‐co‐glycolide) (MC/PLGA) and methylcellulose/poly(1, 4‐butylene succinate) (MC/PBS). The effects of MC/PLGA and MC/PBS mass ratios on the morphology, crystalline state, mechanical properties and thermal stability of the composite films were systematically investigated. At the same time, the influence of thermal compression treatment on mechanical properties (tensile strength and elongation) and the cyclic utilization of the composite films were also estimated. The composite films displayed enough good mechanical properties, re‐usability and thermal stability. Abstract :